Penetration and development ofPratylenchus brachyurusin maize roots treated with acibenzolar-S-methyl - Puerari, H. H. (2020)
The aim of this study was to evaluate the application of acibenzolar-S-methyl (ASM) in the penetration, development, and multiplication ofP. brachyurusin maize. For this, maize seedlings cv. AL Bandeirantes, after 10 days of germination, were inoculated with 800 nematodes. Part of the plants were treated with ASM sprayed at the dose 0.25 g a.i. L-1, while another part were inoculated but not treated. Every five (experiment 1) and two (experiment 2) days after treatment (DAT), the plants were removed, the roots washed and stained with acid fuchsin for counting nematodes. The nematodes were also quantified at 30 and 60 DAT, and their length measured using an eyepiece graticule coupled to the optical microscope, in which the nematodes were classified in three groups: 0.10 to 0.29, 0.30 to 0.49 and 0.50 to 0.69 mm. ASM reduced the final nematode population in maize roots at 30 and 60 DAT, and the number of juveniles, adults and eggs in the plant root system at 8 and 10 DAT. In relation to the nematode development, an increase in the proportion of nematodes at an early stage (0.10 to 0.29 mm) and a lower proportion of nematodes presenting between 0.50 and 0.65 mm of length were observed in plants treated with ASM compared to control. Therefore, results suggest that the product studied may affect the development and reproduction of the nematode.